Anti-corrosion and anti-leakage glue, preparation method and lead-acid storage battery
By using an anti-corrosion and leakage-proof glue composed of toluene, polyisobutylene, polyethylene, styrene and hydrogenated rosin on the lead-acid battery terminal, the problem of intimate sealing between the lead alloy terminal and the plastic cover is solved, and the service life and sealing performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411665099.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-25
AI Technical Summary
The seal between the lead alloy terminal and the plastic cover of the lead acid battery is not tight, which leads to acid corrosion of the acid liquid, which in turn leads to terminal corrosion and breakage, affecting the service life of the battery.
A corrosion-proof and leak-proof glue was developed to prepare glue suitable for the use environment of lead-acid battery by combining toluene, polyisobutylene, polyethylene, styrene and hydrogenated rosin, and applied to the terminal surface to enhance sealing and block corrosion.
It effectively reduces the corrosion of sulfuric acid on the lead column, blocks the corrosion spread of lead alloy, greatly improves the service life of the terminal, and improves the sealing performance of the lead-acid battery.
Smart Images

Figure BDA0005144399780000101 
Figure BDA0005144399780000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lead-acid batteries, and in particular to an anti-corrosion and anti-leakage glue, a preparation method and a lead-acid battery. Background Art
[0002] Lead-acid batteries have the characteristics of high safety, low requirements for use conditions, and large discharge current. They are widely used in energy storage, backup power, automotive power, and automotive start-stop. The positive and negative terminals of lead-acid batteries are mostly lead alloy structures, and the terminals are sealed with battery plastic covers or resin glue. However, the bond between lead alloy and plastic or resin glue is still not tight enough, and the acid inside the battery often creeps along the surface of the lead alloy, eventually causing the battery to leak acid from the terminal or the terminal to corrode and break and lose its conductive function. This type of problem has been highly valued by many researchers engaged in lead-acid batteries. By improving the threaded structure of the terminal or the lead sleeve, the sealing and acid creeping problems of the terminal have not been fundamentally solved, especially the lead alloy structure that needs to be embedded in the battery cover, and there is still a risk of increasing the gap between the lead alloy and the plastic cover. Summary of the invention
[0003] In order to solve at least one of the above technical problems, an invention is developed (purpose of the invention). The present application provides an anti-corrosion and anti-leakage glue, a preparation method and a lead-acid battery.
[0004] On the one hand, the present application provides an anti-corrosion and anti-leakage glue, which is prepared by including the following components in parts by weight:
[0005] Toluene 60-95 parts;
[0006] 1-10 parts of polyethylene;
[0007] Styrene 0.1-5 parts;
[0008] 1 to 10 parts of polyisobutylene;
[0009] 1-10 parts of hydrogenated rosin;
[0010] 0.1 to 5 parts of color powder.
[0011] Optionally, the present application provides a glue prepared from the following components in parts by weight:
[0012] Toluene 70-80 parts;
[0013] Polyethylene 5-7 parts;
[0014] 2-3 parts of styrene;
[0015] Polyisobutylene 5-7 parts;
[0016] 4-6 parts of hydrogenated rosin;
[0017] 2 to 3 parts of color powder.
[0018] Optionally, the weight ratio of toluene to polyethylene is 10 to 16:1.
[0019] Optionally, the toner is lipophilic toner.
[0020] Optionally, the toner is an azo pigment.
[0021] In a second aspect, the present application provides a method for preparing the above-mentioned glue, comprising the following steps:
[0022] S1. Add toluene into a sealed container and heat to 70-80°C;
[0023] S2, cut polyisobutylene into small pieces, add them into the sealed container in S1, and stir them for 5 to 10 hours;
[0024] S3, adding polyethylene, styrene and hydrogenated rosin into the sealed container in S2, stirring at a temperature of 100 °C; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature;
[0025] S4. Add the color powder into the sealed container in S3 and stir for 5 to 30 minutes.
[0026] In a third aspect, the present application provides a lead-acid battery, comprising a terminal, wherein the terminal and the plastic cover are bonded with the glue described in claim 1.
[0027] Optionally, the glue is applied to the terminal surface by smearing.
[0028] In summary, the present invention includes at least one of the following beneficial technical effects:
[0029] 1. By adjusting the amount of toluene, polyisobutylene, polyethylene, styrene and hydrogenated rosin added, the prepared glue can adapt well to the use environment of lead-acid batteries, effectively reduce the corrosion of sulfuric acid on the lead column, block the corrosion of lead alloy and greatly improve the service life of the terminal;
[0030] 2. The glue prepared in this application is in liquid form, which can be easily applied to the terminal surface, so that the terminal surface is evenly covered with a layer of glue film as thin as 0.01 mm. It can effectively reduce the looseness between the lead terminal and the plastic cover and increase the sealing between the terminal and the plastic cover. At the same time, it can quickly dry and solidify, effectively improving production efficiency. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products. Specific embodiments
[0034] Preparation Example 1
[0035] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0036] Add 60g toluene into a sealed container and heat to 75°C; cut 10g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 10g polyethylene, 5g styrene and 10g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0037] Preparation Example 2
[0038] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0039] Add 65g toluene into a sealed container and heat to 75°C; cut 8.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 8.5g polyethylene, 4g styrene and 8g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 4g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0040] Preparation Example 3
[0041] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0042] Add 70g toluene into a sealed container and heat to 75°C; cut 7g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 7g polyethylene, 3g styrene and 6g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 3g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0043] Preparation Example 4
[0044] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0045] Add 75g toluene into a sealed container and heat to 75°C; cut 6.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0046] Preparation Example 5
[0047] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0048] Add 80g of toluene into a sealed container and heat to 75°C; cut 5g of polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 5g of polyethylene, 2g of styrene and 4g of hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2g of color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0049] Preparation Example 6
[0050] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0051] Add 85g toluene into a sealed container and heat to 75°C; cut 3g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 3g polyethylene, 1g styrene and 3g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 1g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0052] Preparation Example 7
[0053] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0054] Add 90g toluene into a sealed container and heat to 75°C; cut 1.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 1.5g polyethylene, 0.5g styrene and 2g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 0.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0055] Preparation Example 8
[0056] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0057] Add 95g toluene into a sealed container and heat to 75°C; cut 1g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 1g polyethylene, 0.1g styrene and 1g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 0.1g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0058] Examples 1 to 8
[0059] The anti-corrosion and anti-leakage glue prepared in the above-mentioned Preparation Examples 1 to 8 was applied to the terminals respectively to make a battery cover.
[0060] Comparative Example 1
[0061] Blank terminals were prepared without adding glue between the terminals and the plastic cover.
[0062] Comparative Example 2
[0063] The glue-wrapped terminal is prepared by using the existing glue-wrapping technology.
[0064] The battery covers prepared in the above Examples 1 to 8 and Comparative Examples 1 to 2 were tested for sealing and corrosion resistance, and the testing method was as follows: the battery covers were immersed in 1.32 g / mL (25°C) acid solution, and left standing at 60°C for 24 hours, -18°C for 24 hours, 60°C for 24 hours, 105°C for 12 hours, -35°C for 12 hours, and 60°C for 12 hours. The test results are shown in Table 1.
[0065] If the thread is not corroded, it means that the terminal has good corrosion resistance and the sealing performance is still reliable. If the thread is corroded, the sealing performance will be reduced;
[0066] The absence of corrosion spots on the thread surface indicates that the terminal has good corrosion resistance. A small amount of corrosion spots does not affect the sealing performance of the terminal, but means that the service life of the terminal will be reduced. If large areas of corrosion appear and the thread surface loses its metallic luster, it means that the corrosion is serious, the sealing performance will be greatly affected, and the service life will be greatly reduced.
[0067] Table 1
[0068] Battery cover glue Weight ratio of toluene to polyethylene Thread corrosion Thread surface corrosion Example 1 Preparation Example 1 6.00 No thread corrosion There are corrosion spots Example 2 Preparation Example 2 7.65 No thread corrosion There are corrosion spots Example 3 Preparation Example 3 10.00 No thread corrosion No corrosion spots Example 4 Preparation Example 4 11.54 No thread corrosion No corrosion spots Example 5 Preparation Example 5 16.00 No thread corrosion No corrosion spots Example 6 Preparation Example 6 28.33 No thread corrosion There are corrosion spots Example 7 Preparation Example 7 60.00 No thread corrosion There are corrosion spots Example 8 Preparation Example 8 95.00 No thread corrosion There are corrosion spots Comparative Example 1 none Three-layer thread corrosion No metallic luster Comparative Example 2 Glue wrap One layer of thread corrosion No metallic luster
[0069] It can be seen from Table 1 that the battery cover is made by applying the glue prepared in the present application, and the sealing corrosion resistance of the battery cover is very good, the three-layer thread is not corroded, the thread surface has slight corrosion spots, and the thread surface of the battery cover corresponding to Examples 3 to 5 has no corrosion spots.
[0070] To further analyze the effect of the weight ratio of toluene to polyethylene on the performance of the glue of the present application, the inventors prepared the following Preparation Examples 9 to 17.
[0071] Preparation Example 9
[0072] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0073] Add 75g toluene into a sealed container and heat to 75°C; cut 8.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0074] Preparation Example 10
[0075] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0076] Add 75g toluene into a sealed container and heat to 75°C; cut 8g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0077] Preparation Example 11
[0078] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0079] Add 75g toluene into a sealed container and heat to 75°C; cut 7.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0080] Preparation Example 12
[0081] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0082] Add 75g toluene into a sealed container and heat to 75°C; cut 7g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0083] Preparation Example 13
[0084] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0085] Add 75g toluene into a sealed container and heat to 75°C; cut 6g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0086] Preparation Example 14
[0087] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0088] Add 75g toluene into a sealed container and heat to 75°C; cut 5.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0089] Preparation Example 15
[0090] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0091] Add 75g toluene into a sealed container and heat to 75°C; cut 5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0092] Preparation Example 16
[0093] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0094] Add 75g toluene into a sealed container and heat to 75°C; cut 4.5g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0095] Preparation Example 17
[0096] This preparation example is used to prepare an anti-corrosion and anti-leakage glue, and the details are as follows.
[0097] Add 75g toluene into a sealed container and heat to 75°C; cut 4g polyisobutylene into small pieces, add into the sealed container, keep warm and stir for 8h; add 6.5g polyethylene, 2.5g styrene and 5g hydrogenated rosin into the sealed container, keep warm and stir; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; add 2.5g color powder into the sealed container, stir for 10min to obtain anti-corrosion and anti-leakage glue.
[0098] Examples 9 to 17
[0099] The anti-corrosion and anti-leakage glue prepared in the above-mentioned Preparation Examples 9 to 17 was applied to the terminals respectively to make battery covers.
[0100] The battery covers prepared in the above Examples 9 to 17 were tested for sealing and corrosion resistance, and the testing method was as follows: the battery covers were immersed in 1.32 g / mL (25°C) acid solution, and allowed to stand at 60°C for 24 hours, -18°C for 24 hours, 60°C for 24 hours, 105°C for 12 hours, -35°C for 12 hours, and 60°C for 12 hours. The test results are shown in Table 2.
[0101] Table 2
[0102]
[0103]
[0104] It can be seen from Table 2 that in the technical solution of the present application, when the weight ratio of toluene to polyethylene is in the range of 10 to 16:1, the prepared glue is used to make the battery cover in a smearing manner, and the sealing and corrosion resistance of the battery cover is relatively better, the three-layer thread is free of corrosion, and there are no corrosion spots on the thread surface.
[0105] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. An anti-corrosion and anti-leakage glue, characterized in that: The invention is prepared by comprising the following components in parts by weight: Toluene 60-95 parts; 1-10 parts of polyethylene; Styrene 0.1-5 parts; 1 to 10 parts of polyisobutylene; 1-10 parts of hydrogenated rosin; 0.1 to 5 parts of color powder.
2. The glue according to claim 1, characterized in that The invention is prepared by comprising the following components in parts by weight: Toluene 70-80 parts; Polyethylene 5-7 parts; 2-3 parts of styrene; Polyisobutylene 5-7 parts; 4-6 parts of hydrogenated rosin; 2 to 3 parts of color powder.
3. The glue according to claim 1, characterized in that The weight ratio of toluene to polyethylene is 10-16:
1.
4. The glue according to claim 1, characterized in that: The toner is lipophilic toner.
5. The glue according to claim 1, characterized in that: The toner is an azo pigment.
6. A method for preparing the glue according to claim 1, characterized in that: The following steps are involved: S1. Add toluene into a sealed container and heat to 70-80°C; S2, cut polyisobutylene into small pieces, add them into the sealed container in S1, and stir them for 5 to 10 hours; S3, adding polyethylene, styrene and hydrogenated rosin into the sealed container in S2, stirring at a temperature of 100 °C; when the solution is stirred until there is no suspended matter, stop heating and cool to room temperature; S4. Add the color powder into the sealed container in S3 and stir for 5 to 30 minutes.
7. A lead-acid battery, characterized in that: The invention comprises a terminal, wherein the terminal and the plastic cover are bonded with the glue described in claim 1.
8. The lead-acid battery according to claim 7, characterized in that: The glue is applied on the terminal surface in a smearing manner.